Nascent and Infant Entrepreneurs in Germany. Evidence from the Regional Entrepreneurship Monitor (REM) - Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2005)
Based on data from a recent representative survey of the adult population in Germany this paper documents that the patterns of variables influencing nascent and infant entrepreneurship are quite similar and broadly in line with our theoretical priors – both types of entrepreneurship are fostered by the width of experience and a role model in the family, and hindered by risk aversion, while being male is a supporting factor. Results of this study using cross section data are in line with conclusions from longitudinal studies for other countries finding that between one in two and one in three nascent entrepreneurs become infant entrepreneurs, and that observed individual characteristics – with the important exception of former experience as an employee in the industry of the new venture - tend to play a minor role only in differentiating who starts and who gives up.
Keywords: Entrepreneur; Germany; Deutschland; Unternehmer; Unternehmensgründung; 331 Arbeitsökonomie